2008
DOI: 10.1016/j.marpolbul.2007.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bioturbation by Hediste diversicolor on mercury fluxes from estuarine sediments: A mesocosms laboratory experiment

Abstract: Mercury, with its reactive forms being the most deleterious for the trophic chains, has been identified as a major pollutant in a few confined bodies of the coastal zone. Due to feeding, burrowing, and bioirrigation activities, infauna are known to play a crucial role in the biogeochemical processes of contaminants. The main goal of the present study is to evaluate the effects of Hediste diversicolor bioturbation on mercury fluxes from estuarine sediments in a mesocosms laboratory experiment. Additionally, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
0
16
0
4
Order By: Relevance
“…Além disso, o processo de transporte e deposição/sedimentação do material particulado em suspensão dependerá também de um conjunto de fatores físico-químicos, que incluem além da salinidade, o tempo de residência das águas, a baixa velocidade de fluxo de corrente, potencial redox, pH, teor de matéria orgânica, tamanho das partículas, concentração de sulfetos e presença de bactéria sulfatoredutoras (Machado 2004;Cardoso et al 2008;Reboreda et al 2008). Segundo os autores ainda, ambientes aquáticos com maior tempo de residência ou que não apresentam competência de transporte possibilitam a deposição do material particulado em suspensão no sedimento, ficando a biodisponibilidade dos metais associados controlada aos fatores físico-químicos supracitados.…”
Section: Transporte E Sedimentação Metálicaunclassified
“…Além disso, o processo de transporte e deposição/sedimentação do material particulado em suspensão dependerá também de um conjunto de fatores físico-químicos, que incluem além da salinidade, o tempo de residência das águas, a baixa velocidade de fluxo de corrente, potencial redox, pH, teor de matéria orgânica, tamanho das partículas, concentração de sulfetos e presença de bactéria sulfatoredutoras (Machado 2004;Cardoso et al 2008;Reboreda et al 2008). Segundo os autores ainda, ambientes aquáticos com maior tempo de residência ou que não apresentam competência de transporte possibilitam a deposição do material particulado em suspensão no sedimento, ficando a biodisponibilidade dos metais associados controlada aos fatores físico-químicos supracitados.…”
Section: Transporte E Sedimentação Metálicaunclassified
“…Metals coprecipitated with or absorbed to FeS and MnS are rapidly oxidized following sediment resuspension, due to their relative solubility in oxic conditions (Allen et al, 1993;Caetano et al, 2003). Also, organic matter has a relevant role since its structural features allow its interaction with substances like metals, modifying its mobility and availability to organisms (Cardoso et al, 2008). Thallium may also exist in the sediments precipitated as sulfides or associated with Fe and Mn sulfides.…”
Section: Thallium In the Overlying Watermentioning
confidence: 99%
“…Jiang et al (2010) compared bioturbation efficiency in Chironomus plumosus and Tanypus chinensis both of arthropoda; the authors demonstrated that the two organism types differ greatly in their feeding and burrowing activities, and certain Chironomid species may play important roles in driving nutrient cycling. Other researchers (Cardoso et al, 2008;Michaud et al, 2006) found that the gallery-diffusers (e.g., Hediste diversicolor) have greater effects than biodiffusers (e.g., bivalves) on the biochemical processes in marine sediment. Gallery-diffuser animals produce diffusion in the layer with very dense gallery systems and a bio-transport at the end of the burrows.…”
Section: Introductionmentioning
confidence: 99%
“…However, most earlier studies addressed the effectiveness of AC on remediation of HOCs contaminated sediment (Cho et al 2009;Kupryianchyk et al 2013), whereas the effectiveness on heavy metals has been studied less frequently. Bioturbation can influence the fate, transport, and bioavailability of sediment-bound heavy metals (Ciutat and Boudou 2003;Schaller 2014), it may be responsible for a major fraction of the pollutants released from sediments to the water column (Cardoso et al 2008;Josefsson et al 2010;Thibodeaux and Bierman 2003). In addition, bioturbation may affect sediment remediation processes because it is a main process controlling mobilization of elements including dissolved organic carbon (DOC) from sediments (Schaller 2014).…”
Section: Introductionmentioning
confidence: 99%